Modelo ProLab: ErgoTech, soluciones ergonómicas inteligentes - Temoche Erquiaga, Paola Isabel (2025)
Administrative work, whether in-person or remote, is predominantly characterized by prolonged seated tasks, such as extended meetings and continuous computer use, which pose a significant risk for the development of musculoskeletal disorders. Research has established a correlation between prolonged sitting time and musculoskeletal discomfort, particularly in the lower back (Arippa et al., 2022). In this context, the exposure of administrative workers to ergonomic risks has been identified as a relevant social issue, with potential adverse effects on their health, non-compliance with occupational health and safety regulations, and increased costs for companies due to productivity losses and absenteeism. About it, the present thesis proposes ErgoTech, a consultancy firm that provides comprehensive ergonomic solutions aimed at mitigating ergonomic risks in administrative tasks. The solution consists of a virtual platform and a mobile application powered by artificial intelligence (AI), enabling the integral management of ergonomic assessments, workstation design, continuous monitoring, and active break program administration; the goal is to foster a healthier and more efficient work environment. This business model aligns with SDG 3: Good Health and Well-being and SDG 8: Decent Work and Economic Growth. The results demonstrate the economic and social feasibility and sustainability of the project, with a financial NPV of S/ 3’854,625, an IRR of 269.43%, and a social NPV of S/ 3’651,886 over a five-year period. Therefore, the implementation of ErgoTech is recommended, as it addresses a critical occupational need while representing an opportunity to enhance the well-being of administrative workers and manage ergonomic risks, reduces the incidence of musculoskeletal disorders, promotes optimal working conditions, enhances productivity, and ensures compliance with current regulations. ErgoTech sets a precedent in the application of advanced technology for occupational health and ergonomic risk prevention.